Dysert O'Dea Caslte
The archway of this doorway had been rebuilt in a later church, but its architecture comes from exactly similar sources in Romanesque Italy as those built by the Normans in England. In particular, the structural device used by Roman engineers, that of spanning with a series of concentric orders (later exploited for their decorative possibilities), can be seen here.